Incidental finding of synchronous pleomorphic salivary adenoma and Warthin's tumour within a parotid gland. Issue 4 (24th April 2019) - Horisk, Neil; Stephenson, Eleanor; Sayers, Craig; Reid, Jonathon
Abstract : The presence of two histologically distinct lesions within the same salivary gland is rare. The majority of lesions detected in salivary glands are benign and unifocal. Ultrasound scans and MRI imaging may not detect separate lesions that are in close proximity and this presents a challenge for radiologists and surgeons in the diagnosis of salivary gland lesions. We present a case when incidentally two distinct lesions were discovered during extracapsular dissection of a suspected pleomorphic salivary adenoma. We aim to highlight the difficulty in diagnosing these rare entities using existing investigative techniques.